Cervical ectopic pregnancy treated with methotrexate - Solís, Hugo (2015)
The cases of two patients with cervical ectopic pregnancy with fertility desire depreservación treated with methotrexate (MYX) single dose -50 mg / m2 is presented. The findings as well as treatment and evolution is discussed.